EVALUASI KEBIJAKAN REVITALISASI PASAR TRADISIONAL (STUDI KASUS PASAR SAMPAY KABUPATEN LEBAK) - Jumanah, Jumanah; Sanjaya, Natta; Mulyani, Ipah (Sawala : Jurnal Administrasi Negara, 2019)
Local governments hold economic based policies of one another through the revitalization of traditional markets. But the problems found in the field and the basis of important reasons to be researched because there is a problem that is, the first available buildings such as stores and both have not been filled, second lack of customer compliance in complying with regulations, third Market manager has not been adequate in terms of quantity, parking in the market is not well managed, parking is premanism and not managed by the market, obscurity in the market retribution, the five rental costs are given variatively but There are some traders who don't last long.  This research aims to determine and assess the trade market revitalization policy as well as its impact on the market Sampay district of Lebak, this researcher uses evaluation indicators namely: effectiveness, adequacy, equalization, responsiveness, accuracy and impact of the policy. The method of research is to use qualitative descriptive. The results of this study showed that the evaluation policy of revitalization of traditional markets (case studies in the market Sampay District Lebak has been successful and has a social impact it can be seen from aspects of (1) responsiveness, society responds well The existence of this market, (2) social impact, that is, change the shopping behavior of shopping habits in the modern market into shopping in the traditional market.Keyword : Impact evaluation, market revitalization policy